Chromatin-based epigenetics of adult subventricular zone neural stem cells - Gonzales-Roybal, Gabriel; Lim, Daniel (Frontiers in Genetics, 2013)
In specific regions of the adult mammalian brain, neural stem cells (NSCs) generate new neurons throughout life. Emerging evidence indicate that chromatin-based transcriptional regulation is a key epigenetic mechanism for the life-long function of adult NSCs. In the adult mouse brain, NSCs in the subventricular zone (SVZ) retain the ability to produce both neurons and glia for the life of the animal. In this review, we discuss the origin and function of SVZ NSCs as they relate to key epigenetic concepts of development and potential underlying mechanism of chromatin-based transcriptional regulation. A central point of discussion is how SVZ NSCs – which possess many characteristics of mature, non-neurogenic astrocytes – maintain a “youthful” ability to produce both neuronal and glial lineages. In addition to reviewing data regarding the function of chromatin-modifying factors in SVZ neurogenesis, we incorporate our growing understanding that long noncoding RNAs (lncRNAs) serve as an important element to chromatin-based transcriptional regulation, including that of SVZ NSCs. Discoveries regarding the epigenetic mechanisms of adult SVZ NSCs may provide key insights into fundamental principles of adult stem cell biology as well as the more complex and dynamic developmental environment of the embryonic brain.